KONTRIBUSI PEREMPUAN HINDU TERHADAP PENDAPATAN RUMAH TANGGA (STUDI KASUS PEDAGANG PEREMPUAN DI PASAR KERENENG KOTA DENPASAR) - Ni Kadek Dewi Wianjani; Ni Made Tisnawati (Universitas Udayana, 2023)
Hindu women who are married have a domestic role as wives, but are currently also participating in economic activities as workers to make ends meet. The purpose of this study was to analyze 1) the contribution of Hindu women to household income, 2) the simultaneous and partial effect of the number of family dependents, intensity of traditional and religious activities, husband's income, length of business, and working hours on the contribution of Hindu women to household income households, 3) the role of working hours in moderating the influence of the intensity of traditional and religious activities on the contribution of Hindu women to household income. The sample size of this study was 154 Hindu women traders at Kereneng Market. This research used moderation regression analysis (MRA) technique. The results of this study concluded that the average Hindu woman contributed 59.6 percent to household income. Hindu women's contribution to household income is significantly influenced simultaneously by the number of family dependents, the intensity of traditional and religious activities, husband's income, length of business, working hours devoted to the number of family dependents, intensity of traditional and religious activities and husband's income partially have a negative and significant effect. Length of business and work hours partially have a positive and significant effect. The amount of working hours moderates, that is, strengthens the influence of the intensity of traditional and religious activities on the Contribution of Hindu Women to Household Income.